2008
DOI: 10.1063/1.3021285
|View full text |Cite
|
Sign up to set email alerts
|

Continuous spin mean-field models: Limiting kernels and Gibbs properties of local transforms

Abstract: We extend the notion of Gibbsianness for mean-field systems to the set-up of general (possibly continuous) local state spaces. We investigate the Gibbs properties of systems arising from an initial mean-field Gibbs measure by application of given local transition kernels. This generalizes previous case-studies made for spins taking finitely many values to the first step in direction to a general theory, containing the following parts: (1) A formula for the limiting conditional probability distributions of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 26 publications
0
36
0
Order By: Relevance
“…Therefore, if we have at least two optimal trajectories conditioned to arrive at a certain magnetization m * at time T > 0, and these trajectories can be selected by approximating the magnetization appropriately, then we have an essential discontinuity at m = m * of the conditional distribution m → μ F n (t)(dx 1 |m) as a function of the magnetization m = (1/n) n i=2 x i . Such a discontinuity is referred to as non-Gibbsianness in the meanfield context, see [5,7] for more details.…”
Section: I(a) Is Strictly Convex: No Bad Configurations Indeed In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if we have at least two optimal trajectories conditioned to arrive at a certain magnetization m * at time T > 0, and these trajectories can be selected by approximating the magnetization appropriately, then we have an essential discontinuity at m = m * of the conditional distribution m → μ F n (t)(dx 1 |m) as a function of the magnetization m = (1/n) n i=2 x i . Such a discontinuity is referred to as non-Gibbsianness in the meanfield context, see [5,7] for more details.…”
Section: I(a) Is Strictly Convex: No Bad Configurations Indeed In Tmentioning
confidence: 99%
“…Multiple histories were then shown to lead to jumps in conditional probabilities indicating non-Gibbsian behavior in the mean-field setting, see e.g. [5,7,14]. These special conditionings leading to multiple histories are the analogue of "bad configurations" (essential points of discontinuity of conditional probabilities of the measure at time t ) in the (lattice) Gibbs-non-Gibbs transition scenario.…”
mentioning
confidence: 98%
“…Bad configurations can be characterized explicitly (with the interesting effect that non-neutral bad configurations can arise below a certain critical temperature). For further developments on mean-field results see also [16], [10].…”
Section: 1 Dynamical Gibbs-non-gibbs Transitionsmentioning
confidence: 99%
“…A particularly fruitful research direction was initiated by Külske and Le Ny [9], who showed that Gibbs-non-Gibbs transitions can also be defined naturally for mean-field models, such as the Curie-Weiss model. Precise results are available for the latter, including sharpness of the transition times and an explicit characterization of the conditional magnetizations leading to non-Gibbsianness (Külske and Opoku [11], Ermolaev and Külske [7]). In particular, the work in [7] shows that in the meanfield setting Gibbs-non-Gibbs transitions occur for all initial temperatures below criticality, both for cooling dynamics and for heating dynamics.…”
Section: Background and Motivationmentioning
confidence: 99%